Packtrain carrying freight outside of the Bartlett Bros. offices, Dawson, Yukon territory, 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows the "Green Tree" and "Dawson Market" Caption on image: "Bartlett Bros Pack Train. Dawson. 1899"